Manajemen Strategi Pengelolaan Dan Pengembangan Eksistensi Perpustakaan Desa Sebagai Pusat Sumber Belajar Terhadap Kebutuhan Masyarakat di Desa Sepit - Ahmad Izzudin; Ayuni Hartika; Suparlan (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2023)
Management in something library no will denied will exist something development because development in something Strategic management is also very necessary. Development in a work process or matter other is something that must be done to reach the goal will be achieved. Study aim: 1) role library as a center source of Study for society, 2) to know strategic management in management and development of library village Narrow. Type of research this is a study with a method of descriptive analysis, researcher data collection uses method observation, interviews, and documentation. Validity of researcher data uses technique triangulation. Data analysis was carried out in three stages namely: from results observation, interviews, and documentation. Conclusion of the study this is: 1) The role of the library as a center source of study, besides as center source Study library as well center information, and innovation because the public is capable of taking advantage of existing libraries in looking for information and can do innovation through the existing libraries. The role of other libraries is also: a receptacle in enlightening generation nation. Library villages have a very important role in public villages for increasing knowledge and skills village community. With its founded library can be a cheap, cheerful, and fast destination for realizing long lifelong education in society. The local community is also capable of utilizing the existing library village as a place to do tasks starting from the public or other communities, fine that student or students. 2) Management and development strategy management library village Tongs Keep going do innovation and development. Start doing management from the facet repair condition room Then addition books will be added little by little, and then start to intertwine cooperation and increase partnerships. Library village it's also a narrow development that starts from the stage library then makes the park read and jumps directly into socialization schools and posyandu are also active on social media and introduce library village tongs by taking pictures of shared activities.